2021
DOI: 10.3389/fimmu.2021.756920
|View full text |Cite
|
Sign up to set email alerts
|

Mannose Treatment: A Promising Novel Strategy to Suppress Inflammation

Abstract: High glucose and fructose intake have been proven to display pro-inflammatory roles during the progression of inflammatory diseases. However, mannose has been shown to be a special type of hexose that has immune regulatory functions. In this review, we trace the discovery process of the regulatory functions of mannose and summarize some past and recent studies showing the therapeutic functions of mannose in inflammatory diseases. We conclude that treatment with mannose can suppress inflammation by inducing reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 56 publications
(84 reference statements)
1
30
0
Order By: Relevance
“…This study determined the mRNA and protein expression levels of IL-1β, IL-6, IL-10, IL-17, TNF-α, G-CSF, and GM-CSF in gingival tissues after D-mannose treatment in periodontitis rats, which showed that D-mannose alleviated gingival in ammation in periodontitis rats in vivo and in vitro. Our ndings added evidence to the opinion that Dmannose treatment is a promising novel strategy to suppress in ammation [17]. Researches prove that there are many immune cells involved in the periodontitis process, producing the in ammatory factors.…”
Section: Discussionsupporting
confidence: 56%
“…This study determined the mRNA and protein expression levels of IL-1β, IL-6, IL-10, IL-17, TNF-α, G-CSF, and GM-CSF in gingival tissues after D-mannose treatment in periodontitis rats, which showed that D-mannose alleviated gingival in ammation in periodontitis rats in vivo and in vitro. Our ndings added evidence to the opinion that Dmannose treatment is a promising novel strategy to suppress in ammation [17]. Researches prove that there are many immune cells involved in the periodontitis process, producing the in ammatory factors.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have indicated that mannose has anti-inflammatory effects on various diseases, such as asthma, colitis and osteoarthritis [ 35 ]. These findings suggest that the administration of mannose could be a potential treatment approach for multiple diseases simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating both aspects mentioned above will further expand the clinical applications of mannose. Although many studies have employed mannose concentrations lower than 40 mmol/L, our CCK-8 experiments revealed that NP cells have a maximum tolerance to mannose at a concentration of 40 mmol/L [ 19 , 35 ]. Therefore, a more precise exploration of the dosing of orally administered mannose is crucial for its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been well summarized in the recent past that mannose is a novel suppressor of inflammation (Zhang et al, 2021), we only emphasize the point that mannose treatment could be a safe and promising strategy to suppress and to treat autoimmunity and asthma. More than that, mannose could also suppress woundinginduced inflammation in skin (Jokela et al, 2013).…”
Section: The Anti-inflammatory Effects Of Mannosementioning
confidence: 99%
“…During the last few years, mannose has been shown to have many physiological benefits and applications, such as suppressing inflammation (Zhang et al, 2021), and suppressing tumor growth and metastasis (Gonzalez et al, 2018). Besides suppressing Type 1 diabetes, asthma and macrophage-mediated inflammation (Zhang et al, 2017;Torretta et al, 2020), a most recent study has shown that mannose can suppress experimental autoimmune encephalomyelitis (EAE) by inducing treg cells, suggesting that Mannose may be a potential adjuvant therapy for multiple sclerosis (MS) (Hwang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%